A facilely synthesized glutathione-functionalized silver nanoparticle-grafted covalent organic framework for rapid and highly efficient enrichment of N-linked glycopeptides. Issue 12 (12th March 2019) - Ma, Yu-Fang; Wang, Li-Juan; Zhou, Ying-Lin; Zhang, Xin-Xiang
Abstract : A functionalized covalent organic framework was facilely synthesized via an easily popularized process for highly efficient enrichment of N-linked glycopeptides. Abstract : The development of facilely synthetic materials for highly efficient enrichment of N-linked glycopeptides is essential in glycoproteome analysis. In this work, by utilizing the self-assembling of glutathione (GSH) on silver nanoparticles (Ag NPs), and the formation and dispersion of Ag NPs on a robust TpPa-1 substrate, a newly functionalized covalent organic framework (COF) called TpPa-1@Ag@GSH was synthesized via a simple two step post-synthetic modification. TpPa-1@Ag@GSH and intermediate products were confirmed and evaluated by nuclear magnetic resonance spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, transmission electron microscopy, scanning electron microscopy-energy dispersive spectroscopy, Brunauer-Emmett-Teller and thermogravimetric analyses. Benefiting from the judicious selection of the substrate, the abundance of binding sites, relatively high affinity between GSH and N-linked glycopeptides, and the multivalent interactions between N-linked glycopeptides and unoccupied surfaces of Ag NPs, this porous material showed great performance in N-linked glycopeptide enrichment. By enriching N-linked glycopeptides in tryptic digests of human serum immunoglobulin G (human IgG) followed by mass spectrometry analysis, our method was proved to have good sensitivity (1 fmol), high selectivity (1 : 1500, human IgG to bovine serum albumin), high binding capacity (160 mg g −1, IgG/TpPa-1@Ag@GSH), ultra-fast capture ability (only 1 min incubation time), and good reusability (at least 5 times). It was also successfully applied to the enrichment of N-linked glycopeptides from complex biological samples. Our work improved the enrichment selectivity of COFs, reached the most rapid capture ability among off-column enrichment materials, and provided a very facile and easily popularized post-synthetic modification route for COFs in glycoproteome analysis.